KAPASITAS KELEMBAGAAN DAERAH DALAM PENYELENGGARAAN PEMERINTAHAN DAN PELAYANAN PUBLIK PASCA PEMEKARAN - Syafrianda Syafrianda; Zaili Rusli; Adianto Adianto (Journal Publicuho, 2021)
This study aims to find out how the capacity of local institutions in administering government and public services after the expansion with a case study in Kulim District, Pekanbaru City, and to find out what factors support institutional capacity in administering government and public services after the division of the sub-district area. This research use desciptive qualitative approach. Primary data were obtained directly through interviews with informants, namely the administrative staff of the regional secretariat of the Mayor of Pekanbaru, the Head of Kulim District, the Village Head of Mentangor, sub-district service staff, and community service recipients in the sub-district. The results of this study indicate that the capacity of regional institutions in administering government and public services after the division in Kulim District is sufficient. This is marked by the implementation of various activities in the sub-district in carrying out government administration, public services, and also empowering the community in Kulim District. The factors that support the institutional capacity of the sub-district after the division include organizational structure, work team, number of human resources, commitment and competence, work experience and seniority, and completeness of supporting infrastructure.AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana kapasitas kelembagaan daerah dalam penyelenggaraan pemerintahan dan pelayanan publik pasca pemekaran dengan studi kasusnya di Kecamatan Kulim Kota Pekanbaru, serta untuk mengetahui faktor-faktor apa saja yang mendukung kapasitas kelembagaan dalam penyelenggaraan pemerintahan dan pelayanan publik pasca pemekaran wilayah kecamatan. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data primer diperoleh langsung melalui wawancara dari informan, yaitu Staf bidang pemerintahan sekretariat daerah walikota pekanbaru, Camat Kulim, Lurah Mentangor, staff pelayanan kecamatan, dan masyarakat penerima layanan di kecamatan. Hasil penelitian ini menunjukkan bahwa kapasitas kelembagaan daerah dalam penyelenggaraan pemerintahan dan pelayanan publik pasca pemekaran di Kecamatan Kulim sudah cukup memadai. Ini ditandai dengan sudah berjalannya berbagai aktifitas kegiatan di kecamatan dalam melaksanakan penyelenggaraan pemerintahan, pelayanan publik, dan juga pemberdayaan kepada masrayakat di Kecamatan Kulim. Adapun faktor-faktor yang mendukung kapasitas kelembagaan kecamatan pasca pemekaran antara lain, struktur organisasi, tim kerja, jumlah SDM yang dimiliki, komitmen dan kompetensi, pengalaman kerja dan senioritas camat, dan kelengkapan sarana prasarana pendukung.     Kata Kunci:  Kapasitas Organisasi, Desentralisasi, Pelayanan Publik